Astrocyte dystrophy in ageing brain parallels impaired synaptic plasticity. Issue 3 (6th March 2021) - Popov, Alexander; Brazhe, Alexey; Denisov, Pavel; Sutyagina, Oksana; Li, Li; Lazareva, Natalia; Verkhratsky, Alexei; Semyanov, Alexey
Abstract: Little is known about age‐dependent changes in structure and function of astrocytes and of the impact of these on the cognitive decline in the senescent brain. The prevalent view on the age‐dependent increase in reactive astrogliosis and astrocytic hypertrophy requires scrutiny and detailed analysis. Using two‐photon microscopy in conjunction with 3D reconstruction, Sholl and volume fraction analysis, we demonstrate a significant reduction in the number and the length of astrocytic processes, in astrocytic territorial domains and in astrocyte‐to‐astrocyte coupling in the aged brain. Probing physiology of astrocytes with patch clamp, and Ca 2+ imaging revealed deficits in K + and glutamate clearance and spatiotemporal reorganisation of Ca 2+ events in old astrocytes. These changes paralleled impaired synaptic long‐term potentiation (LTP) in hippocampal CA1 in old mice. Our findings may explain the astroglial mechanisms of age‐dependent decline in learning and memory. Abstract : Ageing reduces the number and the length of astrocytic processes, astrocytic territorial domains and astrocyte‐to‐astrocyte coupling in the hippocampus. Such dystrophy causes deficits in K+ and glutamate clearance by astrocytes. Enhanced glutamate spillover impairs synaptic long‐term potentiation (LTP) in hippocampal CA1, which may represent the astroglial mechanisms of age‐dependent decline in learning and memory.